Effect of Mental Task on Sex Differences in Muscle Fatigability: A Review - Vymyslický, Patrik; Pavlů, Dagmar; Pánek, David (International journal of environmental research and public health, 2022)
Previous research demonstrated that there are observable sex differences in developing muscle fatigue when mental task during fatiguing activity is present; however, there is no available review on this matter. Therefore, this review aimed to summarize the findings of previous studies investigating the effect of mental task on muscle fatigue in men and women. To conduct the review, we utilized searches using the electronic databases Web of Science, PubMed, Scopus, and EBSCO Cinahl Ultimate. The studies included had no limited publication date and examined the effects of mental task on muscle fatigue in a healthy adult population of any age. The evaluation was performed using the following criteria: time to failure, or subjective scale in various modifications (visual analog scale-VAS, rate of perceived effort-RPE, rate of perceived fatigue-RPF, rate of perceived discomfort-RPD). A total of seven studies met the set criteria, which were subsequently analyzed. Heavy mental task (more demanding math tasks) can reduce the time to failure for both men and women, with the reduction being more pronounced for women than for men. For light mental task (simple math tasks), no reduction in time to failure was observed to a great extent. The mental task in any of the included studies did not affect the subjective perception of fatigue, effort, discomfort, or pain. Although the studies investigating the effect of mental task on sex differences in muscle fatigability are limited, based on our findings we can assume that in jobs requiring heavier mental task, women may be more prone to the faster development of muscle fatigue; thus, employers might consider paying attention to the possibility of adequate rest.
Keywords: Humans; fatigue; svalová únava; Female; dospělí; muscle fatigue; mental task; lidé; Adult; kosterní svaly; ženské pohlaví; Male; sex differences; Sex Characteristics; Muscle, Skeletal; gender differences; Muscle Fatigue; pohlavní dimorfismus; mužské pohlaví